A ruralidade e o desenvolvimento econômico local: o caso dos municípios brasileiros - Renzi, Adriano (2020)
The origin of the research proposal carried out in this thesis stems from the fact that the indices traditionally (IDH-M and IFDM-G) used to assess the level of economic development do not use aspects of rurality, nor do they consider other dimensions of economic development, represented by the set of variables components of the methodology employed by them. As a result, these traditional indices produce estimates and, a posteriori, classifications of municipalities and regions with less explanatory power and veracity to the local reality. Based on the problem identified, the objective of this thesis is to analyze, through two new indices, the rurality economic development index (IDER) and the local economic development index (IDEL), the level of economic development of national municipalities through the breakdown. the dimensions inherent to such a concept and the territorial and spatial characteristics. Thus, the thesis has a descriptive-deductive character and, methodologically, is based on an experimental-explanatory basis. The statistical data used were collected from several sources: agricultural census (2006) and demographic (2010), both circumscribed at IBGE, in addition to data from DATASUS (2010), IPEADATA (2010) and Atlas of Human Development (2013), using multivariate analysis, factor analysis, for the constitution of indexes and, subsequently, classification of municipalities. Then, Exploratory Spatial Data Analysis (ESDA) is used to assess the formation of clusters in relation to the two proposed indexes. The main results obtained come, first, from the indexes that originated, presenting a classification of municipalities that diverged from the traditionally employed indexes and, therefore, offer, in addition to the traditional indexes, results that are more adherent to local characteristics; second, aspects of rurality positively correlate, to some degree, and therefore positively affect and integrate the level of local economic development; thirdly, the formation of clusters to outline the different situations of the Brazilian regions in terms of the level of economic development of rurality and, subsequently, the intensification of divergences in terms of the level of local economic development. In summary, the main contribution of this thesis is to present an empirical result that the aspects of Brazilian rurality are, in some proportion, positively related and represent important particularities of the level of economic development of Brazilian municipalities, but in different forms of agglomeration for the divergent Central-South and North-Northeast regions.